2022
DOI: 10.3390/app12136709
|View full text |Cite
|
Sign up to set email alerts
|

Deep Bite Treatment with Aligners: A New Protocol

Abstract: Deep bites can be treated by the intrusion of anterior teeth and the extrusion of the posterior teeth, or both, according to the exposure of the incisors in the smile. The aim of this paper is to propose a protocol to improve the effectiveness of deep bite treatments. Orthodontic movements are programmed following the “frog staging” protocol for the anterior teeth, the application of retention attachments and the overengineered final setup. Two case reports described the clinical and radiographic changes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…If caught early, WSLs result in reversible lesions. If, on the contrary, the acidic environment is not eliminated or reduced, WSLs can evolve into cavitated lesions ( Figure 2 ) [ 18 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…If caught early, WSLs result in reversible lesions. If, on the contrary, the acidic environment is not eliminated or reduced, WSLs can evolve into cavitated lesions ( Figure 2 ) [ 18 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The considerable drop in salivary pH and rise in plaque index may be one cause of the rise in DMFT index. Because increased salivary flow is associated with a rise of the plaque index, which reduces pH, it does not seem to be good to reduce the possibility of carious lesion occurrence [ 28 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further factors influencing mesiodistal tooth width include racial characteristics, sex and inherited traits [ 18 ]. Lateral cephalograms can be used for skeletal parameters contributing to dental crowding such as effective maxillary and mandibular length, mandibular plane angle, Y axis, lower anterior face height and dental parameters such as axial inclination of the lower incisor, inclination of the lower incisor to the mandibular plane and interincisal angle [ 38 ]. Some authors have found that the use of 2D lateral cephalograms or profile photos for orthodontic measurements may not be adequately accurate.…”
Section: Discussionmentioning
confidence: 99%
“…Early primary molar loss might result in a reduction in arch length, increasing the severity of crowding/malocclusion; therefore, in the affected patient, every effort should be made to preserve the natural leeway space [ 29 ]. The unilateral loss of a primary canine or first molar can result in a significant centerline disparity and mesial migration of the buccal segments, which is another critical clinical condition to preserve space [ 38 ]. Space maintainers are classified into three types: fixed unilateral appliances, fixed bilateral appliances and removable partial dentures.…”
Section: Discussionmentioning
confidence: 99%